EXCLUSIVE BREASTFEEDING AND IT'S CORRELATION WITH DIABETES MELLITUS AND OBESITY CASES IN CHILDREN (CIPEEX, 2022)
BREASTFEEDING IS CAPABLE OF DIMINISHING NOT ONLY POS-NATAL MORTALITY BUT ALSO THE RISK OF DIABETES MELLITUS AND OBESITY BOTH IN MOTHER AND CHILD. HOWEVER, THE LAST EFFECT IS NOT WIDELY KNOWN NOR RESEARCHED. THEREFORE, THE AIM OF THIS STUDY IS TO SYNTHESIZE THE FEW STUDIES ABOUT THE INFLUENCE OF BREASTFEEDING AND THE DEVELOPMENT OF DIABETES AND OBESITY IN CHILDREN. IT IS AN INTEGRATIVE REVIEW OF LITERATURE, IN WHICH THE GUIDING QUESTION WAS MADE BASED ON THE PICO STRATEGY. THE ARTICLES USED WERE OBTAINED FROM RESEARCH IN: €ŒGOOGLESCHOLAR€, €ŒVIRTUAL HEALTH LIBRARY€, €ŒSCIVERSE SCOPUS€, €ŒSCIENCEDIRECT€, €ŒCOORDINATION FOR THE IMPROVEMENT OF HIGHER EDUCATION PERSONNEL€, €ŒWEB OF SCIENCE€ AND €ŒPUBMED€. A TOTAL OF 36 ARTICLES, SPECICALLY ON THE TOPIC, WERE ANALYZED (FIFTEEN RELATED TO DIABETES AND TWENTY-ONE TO OBESITY). TE RESULTS SHOWED THAT BOTH OF THE ILLNESS ARE RELATED TO GENETIC FACTORS AND BODY MASS INDEX (BMI) OF THE MOTHER, BUT ARE ALSO INFLUENCED BY BREASTFEEDING. CONCERNING DIABETES, WITH THE INCREASE ON THE PERIOD OF EXCLUSIVE BREASTFEEDING THE INCIDENCE OF THE TYPE 2 OF SAID ILLNES PROGRESSIVELY AND EXPONENTIALLY DECREASED, ESPECIALLY WHEN THIS HABIT WAS MANTAINED FOR MORE THEN FOUR MONTHS. HOWEVER NO INFLUENCE WAS SEEN ON THE INCIDENCE OF DIABETES TYPE 1, BECAUSE OF IT€™S GENETICAL ORIGINS. ABOUT OBESITY, CHILDREN THAT WERE BREASTFED IN THEIR INICIAL MONTHS OF LIFE SHOWED LOWER BMI, RISK OF OVERWEIGHT AND OBESITY. GIVEN THE RESULTS, THERE IS A POSITIVE CORRELATION BETWEEN BREASTFEEDING AND DIABETES AND OBESITY, THAT INCREASES WITH THE LONGER DURATION OF BREASTFEEDING.
Keywords: aleitamento materno; diabetes mellitus; criança